Chemical and radiological characterization of fly and bottom ash landfill of the former sulfate pulp factory Plaški and its surroundings - Oreščanin, Višnja; Kollar, Robert; Buben, Kresimir; Mikelic, Ivanka Lovrencic; Kollar, Karlo; Kollar, Melkior; Medunic, Gordana (Journal of environmental science and health. Part A, Toxic/hazardous substances & environmental engineering, 2012)
The subject of this study was chemical and radiological characterization of the fly and bottom ash, by-product of the combustion of coal used as an energy source in the former sulfate pulp factory in Plaški. The research involves determination of the concentration of macro, micro and trace elements and activities of the radionuclides in: (i) ash from different positions of the landfill; (ii) soil samples in the zone of the influence of the landfill; (iii) control soil samples and (iv) sediment sample from the river Dretulja. Besides, in situ measurement of an effective dose rate above ash/soil was also determined. In relation with the control soil the average increase of the concentrations of the elements Ca, Cd, Hg, Ni, Se, Sr, Th and U in the samples taken from the fly and bottom ash landfill as well as soil samples within the radius of 300 m from the landfill was 38.3, 6.7, 9.9, 8.5, 9.4, 7.2, 3.6 and 5.7 times, respectively. In these samples, the concentrations of the above mentioned elements were in the following ranges: calcium from 7.94 to 19.7 %; cadmium from 0.33 to 1.66 mg/kg; mercury from 0.18 to 0.49 mg/kg; nickel from 260 to 1500 mg/kg; selenium from 2.7 to 21 mg/kg; strontium from 176 to 542 mg/kg; thorium from 8 to 55 mg/kg and uranium from 5.6 to 19.7 mg/kg. Compared to the world's average soil concentration, uranium and thorium values increased 3.7 and 1.7 times, respectively. The mean value of the total effective dose rate measured in the air at the height of 1 m for all samples of ash and soil under the influence of the landfill was 1.60 mSv/yr. Compared to the Croatian average (0.7015 mSv/yr), the determined mean value for the Plaški landfill is two times higher. However, compared to the local background (0.14 mSv/yr), the mean value of the total effective dose rate measured above the Plaški landfill is 11.4 times higher. In the samples of ash and contaminated soil regardless of the sampling location the activity concentrations of the radionuclides in Bq/kg vary in the following ranges: ²²⁶Ra from 82.10 to 314.90 (mean value 145.99), ²³²Th from 32.50 to 223.60 (mean value 76.76) and ²³⁸U from 69.10 to 243.20 (mean value 134.38). Compared to the mean values found in the background soil ²²⁶Ra and ²³⁸U mean activity concentrations increased from 1.6 to 6.4 times and ²³²Th from 1.4 to 4.3 times. In order to reduce total effective dose rate to the local “background” values and to prevent redistribution of the radionuclides and heavy metals from the deposited material into the environment fly and bottom ash landfill must be sealed with 10 cm thick layer of the material with low permeability.